HUBUNGAN KOORDINASI MATA-KAKI DENGAN KETERAMPILAN MENGUMPAN BOLA PADA TIM SEPAKTAKRAW SMA NEGERI 1 DAYUN - Fatoni Nur Azis; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The problem in this research was lack of capacity in controlling the ball and passing the ball to team mate, their team were often failed to offer feedback when the ball was played in court, when kicking the ball, it could not be controlled to be delivered to smasher. Because without a good passing the ball, it was difficult for teams to organize the attacks from opponent teams. The purpose of this research was to determine whether there is a relationship between eye and foot coordination skills at SepakTakraw team SMA Negeri 1 Dayun. The population in this study were all players of SepakTakraw SMA Negeri 1 Dayun which consisted of 8 players. The technique of sampling was the overall population (total sampling). The Instruments used in this research is to test the coordination of eye and foot, which aimed to measure eye coordination with foot then test operand (passing) aimed to measure the skills to pass the ball out of the sample used. After that, the data was analyzed with statistic, to test for normality test at significant level a0,05 lilifors. The hypothesis showed the relationship between the eye and foot coordination skills in passing the ball. Based on the research results, it can be concluded as follows,Where rcount at significant level α (0,05) = 0.707 means rcount (0,877) > rtab (0.707).Keywords : The Relationship, eye-foot coordination, Passing the ball skills